Highly Efficient Reversible Hydrogenation of Carbon Dioxide to Formates Using a Ruthenium PNP-Pincer Catalyst - Filonenko, Georgy A.; van Putten, Robbert; Schulpen, Erik N.; Hensen, Emiel J. M.; Pidko, Evgeny A. (ChemCatChem, 2014)
The use of hydrogen as a fuel requires both safe and robust technologies for its storage and transportation. Formic acid (FA) produced by the catalytic hydrogenation of CO2 is recognized as a potential intermediate H2 carrier. Herein, we present the development of a formate‐based H2 storage system that employs a Ru PNP‐pincer catalyst. The high stability of this system allows cyclic operation with an exceptionally fast loading and liberation of H2. Kinetic studies highlight the crucial role of the base promoter, which controls the rate‐determining step in FA dehydrogenation and defines the total H2 capacity attainable from the hydrogenation of CO2. The reported findings show promise for the development of practical technologies that use formic acid as a hydrogen carrier. Like pinning down an ant: An Ru PNP catalyst provides unprecedented rates of CO2 hydrogenation up to 1 100 000 h−1 (turnover number >200 000) and excellent activity in the dehydrogenation of formic acid in DMF if used with the non‐nucleophilic 1,8‐diazabicyclo[5.4.0]undec‐7‐ene base. Unlike amine‐based systems, this medium allows us to achieve high formate capacity together with rapid H2 charging and release.